(untitled) (Research, Society and Development, 2022)
The cultivation of microalgae in liquid residues appears as a biotechnological possibility due to the sustainability of the process, since pollutants present in residues such as nitrogen (N) and phosphorus (P) are used by these microorganisms as nutrients for their growth and biomass production with added value. The objective of this work was to develop a prototype of photobioreactors to remove nutrients: nitrogen and phosphorus through the cultivation of microalgae Chlorella vulgaris in landfill leachate diluted in domestic effluent. The cultivation lasted 28 days where the removal of nutrients nitrogen and phosphorus was evaluated, as well as microalgal growth. The best results of algal growth were obtained in photobioreactors containing 100% domestic effluent and 15% slurry with chlorophyll concentration of 2.277,08±247,21 µg.L-1 and 223,12±17,44 µg L-1, respectively, on the 21st day of culture. Regarding the removal of nutrients of nitrogen and phosphorus, it was possible to observe that the species used in this study showed good efficiency, about 72,36% for nitrogen and 44.32% for phosphorus at the end of the cultivation time.